On the Attempt to Unlock the Black Boxes of Science (2) - Poviliūnas, Arūnas; Voznikaitis, Antanas; Mačiulė, Lina; Juknienė, Monika; Sinkevičiūtė, Elena; Žilinskaitė, Rima (Sociologija. Mintis ir veiksmas, 2018)
This article further develops the ideas expressed in our previous publication – On the Attempt to Unlock the Black Boxes of Science (1) – and presents a sociological experiment that aims to break the conventional routine of the research activities of both sociology and life sciences. The article consists of two parts. The first part discusses the concept of “the new scientific spirit,” elaborated by French scientist and philosopher G. Bachelard, and introduces H. White’s theory of tropes, which provides a novel interpretative framework for “the new scientific spirit.” The second part of this article describes a didactic experiment comprised of two discussion groups with PhD students working in the field of life sciences. The first discussion group attempted to realize the principles of the sociology of the social, whereas the second one attempted to break the limits of the sociology of the social and to induce an epistemological rupture in order to realize the principles of the sociology of translation in the second discussion. This article also includes the authors’ reflections regarding the formation of their own sociological habitus.
Keywords: new scientific spirit; non-Cartesian epistemology; tropology; science communication; didactics of sociology